2021
DOI: 10.3390/antiox10091498
|View full text |Cite
|
Sign up to set email alerts
|

Sulfane Sulfur Regulates LasR-Mediated Quorum Sensing and Virulence in Pseudomonas aeruginosa PAO1

Abstract: Sulfane sulfur, such as inorganic and organic polysulfide (HSn− and RSn−, n > 2), is a common cellular component, produced either from hydrogen sulfide oxidation or cysteine metabolism. In Pseudomonas aeruginosa PAO1, LasR is a quorum sensing master regulator. After binding its autoinducer, LasR binds to its target DNA to activate the transcription of a suite of genes, including virulence factors. Herein, we report that the production of hydrogen sulfide and sulfane sulfur were positively correlated in P. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Our findings represent an example of evolutionary trade-offs. P. aeruginosa relies on QS to regulate several functions, including the expression of virulence factors and biofilm development ( 11 , 39 ). The virulence factor LPS acts as a phage receptor that is conducive to phage infection, and its synthesis pathway is positively regulated by QS ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings represent an example of evolutionary trade-offs. P. aeruginosa relies on QS to regulate several functions, including the expression of virulence factors and biofilm development ( 11 , 39 ). The virulence factor LPS acts as a phage receptor that is conducive to phage infection, and its synthesis pathway is positively regulated by QS ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The iSS level in Pseudomonas aeruginosa is high in the late log phase and early stationary phase of growth, and it activates MexR to turn on the expression of a multiple drug efflux pump MexAB when cells enter the stationary phase [ 10 ]. The high levels of iSS in the late log phase and early stationary phase of growth also significantly enhance the activity of the master quorum-sensing activator LasR in P. aeruginosa [ 11 ]. The multidrug repressor MarR is inactivated by increased iSS in the early stationary phase of growth of E. coli [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that in bacteria, the concentration of sulfane sulfur can be higher than 100 μM ( Ran et al 2019 ). It has recently been demonstrated that sulfane sulfur increases the virulence in Pseudomonas aeruginosa PAO1 by targeting its quorum sensing (QS) systems ( Xuan et al 2021 ). However, we recall the long known antimicrobial activity of garlic, for which, as we know today, diallyl sulfides are responsible, which are the source of sulfane sulfur.…”
Section: Resultsmentioning
confidence: 99%